A comparison of intrathecal magnesium and ketamine in attenuating remifentanil-induced hyperalgesia in rats. Issue 1 (December 2015) - Sun, Jiehao; Lin, Hai; Feng, Xiaona; Dong, Jiaojiao; Ansong, Emmanuel; Xu, Xuzhong
Abstract Background Activation of NMDA receptors play an important role in the development of remifentanil-induced hyperalgesia. We hypothesized that in addition to ketamine, intrathecal MgSO4 could also relieve thermal and mechanical hyperalgesia in rats. Methods Initially, 24 Sprague–Dawley rats were divided into control group, remifentanil group, surgical incision group and remifentanil combined with surgical incision group to create an experimental model. Subsequently, 40 rats were divided into control group, model group, model group plus 100 μg MgSO4, 300 μg MgSO4 and 10 μg ketamine respectively. Paw withdrawal mechanical thresholds and paw withdrawal thermal latency tests were performed at −24 h, 2 h, 6 h, 24 h, 48 h, 72 h and 7 day after the surgical procedure. After behavior assessment on the 7th day, remifentanil was given again to ascertain whether or not NMDA antagonists could suppress the re-exposure of remifentanil-induced hyperalgesia. Results Remifentanil administration plus surgical incision induced significant postoperative hyperalgesia, as indicated by decreased paw withdrawal mechanical thresholds and paw withdrawal thermal latency to mechanical and thermal stimulation. In addition to ketamine, intrathecal MgSO4 (100, 300 μg) dose-dependently reduced remifentanil-induced mechanical and thermal hyperalgesia. Ketamine had less mechanical hyperalgesia in 6 h (p  = 0.018), 24 h (p  = 0.014) and 48 h (p  = 0.011) than 300 μg MgSO4 . There was no difference in inhibiting thermal hyperalgesia between the group ketamine and group MgSO4 (300 μg). The rats were given remifentanil again 7 days later after the first exposure of remifentanil. The hyperalgesic effect induced by re-exposure of remifentanil was not reversed in any groups of MgSO4 or ketamine. Conclusions In addition to ketamine, intrathecal administration of MgSO4 dose-dependently reduced remifentanil-induced hyperalgesia in a surgical incision mode. Re-exposure to remifentanil 1 week later again produced hyperalgesia, and this was not altered by the prior intrathecal treatments in any 4 groups treated with MgSO4 or ketamine.